Hepatitis D infection: from initial discovery to current investigational therapies. (23rd June 2019) - Da, Ben L; Heller, Theo; Koh, Christopher
Abstract: Hepatitis D is the most severe form of viral hepatitis associated with a more rapid progression to cirrhosis and an increased risk of hepatocellular carcinoma and mortality compared with hepatitis B mono-infection. Although once thought of as a disappearing disease, hepatitis D is now becoming recognized as a serious worldwide issue due to improvement in diagnostic testing and immigration from endemic countries. Despite these concerns, there is currently only one accepted medical therapy (pegylated-interferon-α) for the treatment of hepatitis D with less than desirable efficacy and significant side effects. Due to these reasons, many patients never undergo treatment. However, increasing knowledge about the virus and its life cycle has led to the clinical development of multiple promising new therapies that hope to alter the natural history of this disease and improve patient outcome. In this article, we will review the literature from discovery to the current investigational therapies.